2008
DOI: 10.1590/s0103-84782008000800023
|View full text |Cite
|
Sign up to set email alerts
|

Otimização da técnica da PCR para a detecção de Actinobacillus pleuropneumoniae

Abstract: Optimization of PCR technique for detection of Actinobacillus pleuropneumoniae RESUMO A utilização de métodos moleculares baseados em PCR é fundamental na detecção do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The apxIVA gene and its product have been frequently used as one of the most important molecular markers in the detection and serodiagnosis of A. pleuropneumoniae (Dreyfus et al, 2004;Yang et al, 2009;Urbaniak & Markowska-Daniel, 2011). The omlA and cpx genes have also been used as markers for A. pleuropneumoniae, but we opted not to use these genes in the present work due to serotype variability and previous problems with nonspecific amplifications, respectively (Gram et al, 2000;Souza et al, 2008). When using the primer pair APXIV-Up and APXIV-Do and the amplification conditions suggested by Costa et al (2004), only 84% of our clinical isolates, which had been previously identified by biochemical tests and characterised by multiplex PCR (Rossi et al, 2013), were positive for the apxIVA DNA fragment.…”
Section: Resultsmentioning
confidence: 99%
“…The apxIVA gene and its product have been frequently used as one of the most important molecular markers in the detection and serodiagnosis of A. pleuropneumoniae (Dreyfus et al, 2004;Yang et al, 2009;Urbaniak & Markowska-Daniel, 2011). The omlA and cpx genes have also been used as markers for A. pleuropneumoniae, but we opted not to use these genes in the present work due to serotype variability and previous problems with nonspecific amplifications, respectively (Gram et al, 2000;Souza et al, 2008). When using the primer pair APXIV-Up and APXIV-Do and the amplification conditions suggested by Costa et al (2004), only 84% of our clinical isolates, which had been previously identified by biochemical tests and characterised by multiplex PCR (Rossi et al, 2013), were positive for the apxIVA DNA fragment.…”
Section: Resultsmentioning
confidence: 99%